A New Introduction to Islam, 2nd ed.: By Daniel W. Brown (West Sussex, UK: Wiley-Blackwell, 2009. pbk. 339 pages) (American Journal of Islam and Society, 2011)
A New Introduction to Islam is an excellent undergraduate textbook presentinga thorough history of Islam. It introduces students to the historyand development of Islamic studies as a discipline—showing how Islamicstudies has shaped our understanding of Islam—and it also examineshow the vibrant religious culture of the Near East produced a unique andbrilliant intellectual and religious tradition spanning the fields of Islamiclaw, theology, philosophy, and mysticism. In addition, it shows the waysin which the Islamic tradition has enriched the world, and in turn, how ithas been enriched by interaction with other civilizations. And against thebackground of social and cultural contexts that extend from North Africato South and Southeast Asia, it also considers the opportunities and challengesfacing Muslims today and provides a new and illuminating perspectiveof the development of Muslim beliefs and practices ...